Prevalence of children’s emotional and behavioural problems and parents’ psychological distress in Child and Adolescent Psychiatric Clinic Hospital Sultan Abdul Aziz Shah - Masiran, Ruziana; Tan, Kit Aun; Ismanizan, Muhammad Afiq; Roslee, Nordiana Alina; Prabaharan, Priyadarshika (Taylor and Francis, 2025)
Objective: There is a growing concern regarding the increasing trend of emotional and behavioural problems (EBP) in children, alongside rising mental health challenges among Malaysian parents. This study aims to delineate the prevalence of EBP in children attending the child and adolescent psychiatric (CAP) clinic at Hospital Sultan Abdul Aziz Shah and assess the levels of psychological distress in their parents. Methods: In this cross-sectional study, 125 parents assessed the severity of their children’s EBP and their own mental health using validated self-administered questionnaires. Results: The prevalence of EBP among children was 48.0%, while the prevalence of depression, anxiety, and stress among their parents was 32.8%, 45.6%, and 32.8%, respectively. Conclusion: In line with global literature, this study emphasises the critical need to address the mental health of parent-child dyads via the implementation of integrated services that manage these intertwined issues.